The response of organic scintillators to neutrons of energy 14-63 MeV - Buffler, A (Department of Physics, 2023)
The response of a 5 cm (diameter) by 5 cm cylindrical NE213 liquid scintillator to neutrons has been measured as a function of neutron energy in the range 15-63 Me V, using time-of-flight to select neutron energy. The response function at each neutron energy was separated into components associated with the emission of different charged particles, identified by pulse · shape dissimilation to be protons, deuterons, and alphas, respectively. The response (light output) of NE213 to protons, deuterons and alphas was measured as a function of energy. Furthermore, total cross sections for neutron-induced proton, deuteron, and alpha production from 12C were determined from the charged particle yields. The simultaneous presence of n-p elastic scattering in the scintillator provided a reference for establishing an absolute cross section scale for the measurements. The results give information about reaction mechanisms and provide an improved basis for determining the neutron detection efficiency of the scintillator as a function of energy over this range.